TYPOLOGY OF CATEGORY CASE IN GERMAN AND UZBEK LANGUAGES (Scientific journal of the Fergana State University, 2024)
One of the important factors of perfect learning of a foreign language is to learn the studied foreign language by comparing it with oneʼs native language. When languages are studied by mixing, their differences and similarities increase the interest of the language learner, and have a positive effect on their memory, the structure and form of languages are interrelated, their differences are more obvious. The grammatical categories of the German and Uzbek languages ​​are one of the important issues in learning the German language and are of great importance when teaching a foreign language. Categories in German and Uzbek languages ​​have their own characteristics. The study of these grammatical categories, their comparative analysis with the German and Uzbek languages, the analysis of their similarities and differences, as well as their results are of great importance in teaching a foreign language. The importance of grammatical categories in teaching a foreign language is also important, especially in the formation and improvement of oral and written speech skills, and their systematic and comparative study is one of the pressing issues. The article describes the category of agreement related to nouns in the German and Uzbek languages, the existing agreements in the German and Uzbek languages, their specific aspects, and the differences between them.